Surface Plasmon Assisted Electron-Hole Migration for High Photocurrent Density Generation in a Perovskite Solar Cell - Mahinder Singh, Balbir Singh (2019)
Zinc oxide (ZnO) has been used widely as a selective electron collector owing to its superior characteristics of high electron mobility and low temperature processability, especially in a perovskite solar cell (PSC).